Analisis Ekonomi Unit Produksi Minyak Goreng Miniplant Politeknik Kampar - Anna Dhora; Nina Veronika; Hanifah Khairiah (Jurnal Sains dan Ilmu Terapan, 2019)
Riau at this time has become one of the provinces with the largest oil palm plantations in Indonesia. This vast oil palm plantation is also offset by the rapid growth of palm oil mills (PKS) in Riau province itself. thus the availability of CPO as a source of raw material for cooking oil in general can be said to be sufficient. Kampar Polytechnic is one of the educational institutions in Riau, precisely in Kampar Regency. Since its inception, this Polytechnic has had a specific goal as an institution capable of producing graduates who have extensive knowledge in the palm oil industry, both upstream and downstream industries. This is what underlies the construction of miniplants or mini factories as part of the Kampar Polytechnic. This miniplant was built with the main objective of being a learning tool for Kampar Polytechnic students to be able to experience the industrial environment on a small scale, especially industries related to the chemical processing of CPO.